(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article considers competence as an important vector of the success of a social worker’s activity, discloses the concept of "competence of a social worker" and this components consisting of the future professional social skills available to the social worker, skills and abilities, personal qualities, and the ability to apply the acquired knowledge, skills and abilities in practice. The results of the research, provided in the article shows that the level of competence of a social worker is determined by the degree of formation of all these elements, their successful combination. Professional competence is defined not only as the amount of knowledge necessary to provide professional assistance and services to individuals, groups, organizations, citizens, but as a certain level of professionalism, inseparable from the set of personal qualities, psychological characteristics that contribute to the creation of individual "professional handwriting", professional style.